Experimental analysis of the metal roofed industrial building using nano-silica disbanded crude wax (NDCW). (2022) - Rinawa, Moti Lal; Pitchandi, P.; Vigneshkumar, N.; Sharma, Rajneesh; Singh, Manoj Kumar; Subbiah, Ram; Kumar, P. Manoj
Abstract: The increased daytime temperature upsurges the energy need of the buildings for space cooling, particularly on days with strong sun exposure. The building's roof adds far more to this reason by allowing a big amount of heat to flow-in during the day. Additionally, single-storey structures with metal roofs allow for increased heat penetration, and so enhance the building's overall heat gain. They could do so by increasing the cooling load in order to achieve human comfort. The present work involved conducting an experiment to see whether a crude wax based Nano-silica (SiO2 ) Disbanded Phase Changing Material (NDCW) might be used to lower the internal temperature of a metal roofed single-story industrial structure effectively. This approach attempted to minimize the building's total cooling load, hence reducing the amount of conventional energy required. The research was conducted using a scaled-down model of the planned building. The trials were done in three phases: normal roof (Normal Roof) without crude wax, with crude wax in the roof (CW Roof), and with NDCW inside the roof (NDCW Roof). The NDCW was prepared by disbanding 1.0% volume of nano-silica within the crude wax. The findings from the investigations shown that encapsulating crude wax and NDCW under the metal roofing of a single-storey structure significantly lowered the exterior roof's temperature, inner roof's temperature, and further enhanced the thermal comfort of the indoor building space. With the assistance of crude wax and NDCW, the daytime mean internal space temperature was decreased by 5 °C and 6 °C, respectively. Further, the corresponding daytime peak was diminished by 10.5 °C and 12.5 °C with crude wax and NDCW, respectively.